Rectify - Season 4 Episode 1-8 - Cady, Patrick; Woods, Kate; Boak, Keith; Keener, R. Derek; Young, Aden; Spencer, Abigail; Clemens, Adelaide (Just Entertainment, 2017)
Season 4, which marks the all-too-soon end of "Rectify's" distinguished run, finds a fresh thematic connection for Daniel while simultaneously setting him free from past complications. More importantly, it gives Daniel an impeccably astute voice rarely heard before and never this magnified. Hitting after a three-year wait in Episode 1, Daniel's articulation of his inner struggles provides a clear mission statement for the end just as it pulls back yet another curtain on this fascinating character, and thus the penetrating series built around him. [www.indiewire.com]
Keywords: Blu-Ray-Disc